Kim - Kipling, Rudyard, 1865-1936. (London : Penguin Books, 1994)
A British orphan disguised as a Hindu combines forces with the dashing horsetrader Red Beard to thwart enemy forces rising against England in 19th century India.
Keywords: India -- History -- 19th century -- Fiction; Adventure stories